Using solar wind data to predict daily GPS scintillation occurrence in the African and Asian low‐latitude regions. Issue 23 (2nd December 2014) - Carter, B. A.; Retterer, J. M.; Yizengaw, E.; Wiens, K.; Wing, S.; Groves, K.; Caton, R.; Bridgwood, C.; Francis, M.; Terkildsen, M.; Norman, R.; Zhang, K.
Abstract: The feasibility of predicting the daily occurrence of Global Positioning System scintillation events using forecasts of common geophysical indices to drive a physics‐based model of the system is demonstrated over a 5 month period for the African and Asian longitude sectors. The output from the Wing K p model, which uses solar wind data to predict the geomagnetic activity level up to 4 h in advance, was used to drive the National Center for Atmospheric Research thermosphere/ionosphere model, from which the strength of the Rayleigh‐Taylor instability growth rate was calculated to determine the likelihood of scintillation. It is found that the physics‐based model demonstrates superior skill to an empirical scintillation model (Wideband Model (WBMOD)) in forecasting scintillation suppression events during seasons when scintillation is common. However, neither of the models driven in this way possess the ability to forecast isolated scintillation events during transitional and off‐peak seasons. Key Points: Geomagnetic activity forecasts used to predict daily EPB occurrence variability Physics‐based and empirical models compared for Asian and African sectors Physics‐based predictions perform best during peak EPB season in both sectors